Comparative analysis of driving forces of land use/cover change in the upper, middle and lower reaches of the Selenga River Basin. (June 2022) - Ren, Yang; Li, Zehong; Li, Jingnan; Dashtseren, A.; Li, Yu; Altanbagana, M.
Abstract: The Selenga River Basin is an important section of the Sino-Mongolian Economic Corridor. It is an important connecting part of the Eurasian Continental Bridge and an important part of Northeast Asia. Comparative analysis of land use changes and their driving forces in the middle and lower reaches of the watershed is an important tool to reveal regional ecosystem changes, which is of great scientific guidance to ensure regional ecological security. This paper takes Selenge County in the upper reaches of Selenga River Basin, Sukhbaatar City in the middle reaches and Ulan-Ude City in the lower reaches as the case areas to compare and analyse the land use change changes based on Landsat remote sensing image data. The partial least squares regression model is used to discuss the driving forces by combining natural and socio-economic factors. The results show the following: (1) Selenge County is overloaded with overgrazing; Sukhbaatar city, as a region with very suitable soil and water conditions in Mongolia, the area of cultivated land is expanding. Since the disintegration of the Soviet Union in Ulan-Ude, the abandonment of farming has been severe due to the reduction of the agricultural population, resulting in a reduction in the area of cultivated land. (2) The upper reaches of the region should focus on preventing overgrazing, which leads to desertification. In the middle reaches, it is necessary to prevent the over-cultivation of cultivated land. In the lower reaches, the damage to the Lake Baikal ecosystem, a natural heritage of mankind, should be prevented by the rapid expansion of urban space. Highlights: Identifying methods for conducting land use studies of cross-border areas. Comparative analysis of land use change between cities. Further comparative analysis of driving forces and recommendations.